Follow-Up Study on Acoustic De-Licing of Atlantic Salmon (Salmo salar): Lepeophtheirus salmonis and Caligus elongatus Dynamics over Four Consecutive Production Cycles - Albert Kjartan Dagbjartarson Imsland; Pablo Balseiro; Sigurd Handeland; Olav Rune Godø (Journal of Marine Science and Engineering)
Acoustic lice treatment (AcuLice) is a newly developed system which uses a composite acoustic sound image with low-frequency sound to remove salmon lice (Lepeophtheirus salmonis) from Atlantic salmon (Salmo salar). The effect of AcuLice treatment on salmon lice dynamics was measured by weekly salmon lice counting at a full-scale production facility from mid-summer 2019 to late-spring 2024. We monitored four production cycles, with AcuLice applied for two of the production cycles and with no AcuLice treatment applied during the other two production cycles as control. This is a follow-up study to our previous work. The numbers of salmon lice treatments and of weeks until the first salmon lice treatment were also compared in the two experimental groups. For the small (sessile and mobile stages) salmon lice, a significantly lower number (mean ± SEM) was shown for the AcuLice group (0.73 ± 0.03) compared with the control group (1.18 ± 0.05). For the mature female salmon lice, a significantly lower number (mean ± SEM) was found for the AcuLice group (0.12 ± 0.01) compared with the control group (0.22 ± 0.03). In addition, the mean (±SEM) number of C. elongatus varied between the two experimental groups and was higher in the control group (0.12 ± 0.01) compared with the AcuLice group (0.03 ± 0.01). In addition, a lower number (mean ± SEM) of salmon lice treatments (1.4 ± 0.17 vs. 4.22 ± 0.20) and a longer production period before the first salmon lice treatment occurred was observed for the AcuLice group (11.2 ± 0.1 weeks) compared with the control group (24.1 ± 2.3 weeks). These data suggest that the use of the AcuLice system significantly reduces the number of salmon lice (by 40–60%) and C. elongatus (by 70%) on farmed Atlantic salmon and reduces the need for traditional salmon lice treatments (by 65%).